Contribution of Islamic law in the discretionary scheme that has implications for corruption - Muhammad Chairul Huda; Budi Ispriyarso (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2019)
This paper explores the studies of the thin line between discretion (freis ermessen) with a criminal act of corruption, using Islamic law’s perspective as one of the law material in Indonesia. Aim of this paper is to make boundaries between discretion which made based on State Administration Product and regulation and help an officer who does discretion will not be trap in a criminal act of corruption through Islamic law’s perspective. This paper purpose four boundaries. First, the boundaries can be seen through understanding the qawāidul fiqhiyyah especially related to governance. Second, act of detournement de povouir (abuse of authority) and abus de droit (arbitrariness) are contradictive with prophetic’s characteristic such as ṣiddiq (honesty), amanah (accountability), tablig (effective communication), faṭonah (smart and heedful). Third, detournement de povouir or abus de droit can categorized as jarimah takzir which can be punish by the authority above them. Fourth, effort to prevent the criminal act of corruption are with uswah leadership, muraqobah, qanaah, and commitment to take care themselves and their family with halal income. For that, public administration can consider using universal values in Islamic Law to help doing discretion without trapped in criminal act of corruption.